Focal myositis and elevated creatine kinase levels in a patient with phaeochromocytoma. Issue 725 (March 1986) - Bhatnagar, D.; Carey, P.; Pollard, A.
Abstract : A case of phaeochromocytoma with marked transient elevation of creatine kinase levels is presented. No obvious cause for the elevation was found in life, but on autopsy a non-specific focal myositis was discovered. Possible reasons for the raised creatine kinase levels and focal myositis are discussed.